2016
DOI: 10.1037/ort0000140
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ early life stressful experiences, their present well-being, and that of their children.

Abstract: Parents' early life stressful experiences have lifelong consequences, not only for themselves but also for their children. The current study utilized a sample of military families (n = 266) including data from both active-duty and civilian parents and their adolescent children. Hypotheses reflecting principles of persistence, transmission, and proximity as pertaining to parents and their children were examined. The impact of parents' childhood experiences on their functioning later in life and, consequently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Yet, the strongest effect of family reintegration was noted for civilian parents' family reintegration and the parent–child relationship ( β = −0.382). The centrality of the civilian parent, more so than the AD parent, is consistent with previous research noting that, in military families, the civilian parent is often more proximal to the child(ren) due to work demands that can limit AD parents' involvement socially, emotionally, and physically, in children's lives (principle of proximity; O'Neal, Richardson, et al, 2016). Interestingly, neither fathers' nor mothers' family reintegration experiences were related to adolescent perceptions of family cohesion, which could suggest that the broader family system (compared to the various relationships comprising the family system as assessed here by IPC and parenting quality) is more stable or resilient when faced with a stressful family reintegration.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Yet, the strongest effect of family reintegration was noted for civilian parents' family reintegration and the parent–child relationship ( β = −0.382). The centrality of the civilian parent, more so than the AD parent, is consistent with previous research noting that, in military families, the civilian parent is often more proximal to the child(ren) due to work demands that can limit AD parents' involvement socially, emotionally, and physically, in children's lives (principle of proximity; O'Neal, Richardson, et al, 2016). Interestingly, neither fathers' nor mothers' family reintegration experiences were related to adolescent perceptions of family cohesion, which could suggest that the broader family system (compared to the various relationships comprising the family system as assessed here by IPC and parenting quality) is more stable or resilient when faced with a stressful family reintegration.…”
Section: Discussionsupporting
confidence: 84%
“…For example, parenting quality is a primary relational attribute with implications for adolescents' adjustment, including their psychosocial health. For various populations, including families in the military and racial/ethnic minorities, studies have repeatedly demonstrated that more positive parenting is linked to less externalizing and internalizing symptoms and more social connections, which supports the relatively universal nature of these associations (Conger et al, 2002; O'Neal, Mallette, Lanier, Mancini, & Huebner, 2016; O'Neal, Richardson, Mancini, & Grimsley, 2016). Similarly, a recent review summarizing a large body of research concluded that children of various ages from toddlers to adolescents who are exposed to IPC are at risk for psychopathology, in part, because of the emotional and physiological consequences of IPC (Harold & Sellers, 2018).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A second explanation is rooted in the potentially dramatically differing connections male military members, on one hand, and female civilian spouses, on the other hand, have relative to the military community and the larger civilian community. Our earlier research on these two “types” of communities indicates there are differences (O'Neal, Mancini et al., ; O'Neal, Richardson et al., ). A third possibility is that the families in the current sample lacked the strong sense of “shared life” that is generally thought to accompany intimate relationships (Elder, Johnson & Crosnoe, ).…”
Section: Discussionmentioning
confidence: 98%
“…Hutchinson () found that adolescents in military families actually engaged in fewer risky behaviors, such as substance use, than other adolescents. Furthermore, in another study the number of work‐related relocations and having a parent deployed in the past year were unrelated to youth mental, physical, and social well‐being after accounting for parents' current well‐being (O'Neal, Richardson et al., ). However, other research indicates that military youth may be more at risk for poor individual outcomes as well as family‐related difficulties, especially during military transition periods (Chandra, Lara‐Cinisomo, et al., ; Huebner, Mancini, Wilcox, Grass, & Grass, ), or due to other military‐related aspects that play a role in their life (i.e., parental military rank, recent relocations; Lucier‐Greer, O'Neal, Arnold, Mancini, & Wickrama, ).…”
Section: Introductionmentioning
confidence: 99%